2016
DOI: 10.1590/s0100-736x2016000100001
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação clínica, laboratorial e anatomopatológica do sistema urinário de ovinos confinados com ou sem suplementação de cloreto de amônio

Abstract: Resumo: A acidificação urinária com cloreto de amônio (CA) é um método preventivo eficiente em urolitíase obstrutiva em ovinos. Os objetivos deste estudo com ovinos confinados, que receberam dieta concentrada com elevado teor proteico, foram: verificar o efeito da dieta sobre a formação de urólitos e o desenvolvimento da doença; analisar as características macroscópicas e histopatológicas do sistema urinário; relacionar os achados clínicos, laboratoriais e necroscópicos com a presença de urólitos. Utilizaram-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
(63 reference statements)
2
9
1
1
Order By: Relevance
“…ureter, which may have contributed to less stone retention at this site (Table 3). These data are consistent with those described by Santarosa et al (2016), who observed unilateral Note. -(*) -significant difference between groups (P < 0.05).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…ureter, which may have contributed to less stone retention at this site (Table 3). These data are consistent with those described by Santarosa et al (2016), who observed unilateral Note. -(*) -significant difference between groups (P < 0.05).…”
Section: Resultssupporting
confidence: 92%
“…The main necropsy findings of the affected animals were a full bladder with extensive area of hemorrhage, necrosis of the urethral process, and dilation of the ureter and renal pelvis (Figure 2), as reported by Lima et al (2009). Santarosa et al (2016) observed hydronephrosis and unilateral dilatation of the ureter in only one sheep without presenting clinical pain symptoms. Uroliths were mostly deposited in the urinary bladder, although they were also found in the renal pelvis and urethra, especially in the sigmoid flexure and the urethral process, the main obstruction points (Figure 3).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations